THE EFFECTIVENESS OF EDMODO AND SCHOOLOGY IN TEACHING SPEAKING - Yuniarti, Nanda Eka; Mulyadi, Dodi; Ifadah, Muhimatul (LPPM Universitas Pancasakti Tegal, 2019)
This study was attempted to describe the effective use of Edmodo and Schoology in teaching speaking and the students? perception of the application practicality in the learning process. It is an experimental study. The subject of the study was eleventh-grade students of MAN N 2 Semarang. There were two groups in this study; experimental group (E) at XI IPA 3 and the control group (C) at XI IPA 5. The research instruments were tests (pre and post-test), questionnaires, and audio documentation. The t-test or value obtained was (0.325) and t result was lower than t table (1.66724). Hence, it can be said that both the learning management system (LMS) using Edmodo and Schoology had equal effects to improve students? speaking performance. It was proved by the mean value of pre-test and post-test, in which the experimental group was 67.71 and 69.71. Meanwhile, in the control group, there were 66.53 and 68.57. Moreover, the result of the questionnaire was 3.40 for students' perception as good criteria related to the practicality in the experimental group. Then, there were 3.42 on good criteria related to the practicality in the control group. It means that the teacher can use either Edmodo or Schoology LMS system in teaching speaking to achieve students? speaking performance, particularly on pronunciation and grammar. In conclusion, Edmodo and Schoology are effective to teach speaking in eleventh graders.